Promoting learning processes for public participation in sustainable development: lessons and experiences from action research in Southern Thailand. (30th March 2006) - Kittitornkool, Jawanit; Burt, Peter
The Masters Program in Environmental Education at the Prince of Songkla University in Southern Thailand has adopted an approach to combining environmental education with community learning. Students are encouraged to take environmental education by conducting participatory action research in collaboration with communities and schools. It includes development of a learning process to suit target groups and facilitation of related community activities. The degree of success depends on the community capital: natural resources; monetary, social, and human capital; and community wisdom. Environmental educators should be aware of the importance of community capital when developing action processes for sustainable development.